Ethnomathematics-Based Learning Tools - Trisnani, Novy; Utami, Wulan Tri Puji (International Journal of Elementary Education, 2021)
The application of the learning from the home system (BDR) and the implementation of social distancing require teachers to develop mathematics learning resources by utilizing an environment close to students' daily lives. However, there are still many teachers who have difficulty developing learning resources that are suitable for students to apply. This study aimed to design a good, practical, and efficient ethnomathematical-based learning device by utilizing Pawon (kitchen) as a learning resource. Learning tools are designed by modifying the Borg and Gall development procedures, namely exploration, planning, development, initial revision, limited trial, final revision, and dissemination. The learning tools developed are then validated by media, material, and cultural experts, which are then tested on three teachers and 12 students. Data collection instruments in the form of exploration sheets and questionnaires. The analysis technique was carried out through quantitative and qualitative descriptive analysis. The study results are that the design of the learning device developed meets the valid criteria as indicated by the percentage of assessments by material experts, media experts, practitioners, and cultural experts in Kulon Progo Regency, which reaches almost 100%. Practicality criteria based on assessments by teachers and students included in the excellent category and effective criteria based on the criteria reference assessment, more than 75% of students get scores above the minimum completeness criteria (KKM). The results of the development of ethnomathematical-based learning tools meet the criteria of being valid, practical, and effective for use in learning mathematics for elementary school students.